Comparison of Orthomosaic Accuracy Based on Unmanned Aerial Vehicle (UAV) Real Time Kinematic (RTK) Radio and RTK NTRIP in Padang City, West Sumatra - Ismail, Muhammad; Wijayanto, Bayu; Sandra, Randi Proska; Prihantarto, Wikan Jaya; Maiyenti, Elisa; Sriharta, M; Fitrian, Rahmat; Putri, Mutiara Amelia (Universitas Negeri Medan, 2025)
UAVs with RTK technology offer high-accuracy aerial mapping, with RTK Radio and RTK NTRIP as two correction methods affecting orthomosaic precision. While previous studies compared these methods in terrestrial surveys, their impact on UAV-based orthomosaics remains underexplored. This research evaluates and compares the accuracy of UAV-derived orthomosaics using RTK Radio and RTK NTRIP to provide practical guidance for optimal mapping applications. This research combined UAV RTK photogrammetry and GIS to produce high-precision aerial maps in two areas of Padang City with different topographies. Data were collected using DJI Mavic 3 Enterprise RTK with RTK Radio and RTK NTRIP techniques, supported by GCPs, BMs, and satellite imagery, then processed into orthomosaics for analysis. Accuracy was assessed using ICPs and statistical measures like RMSE to compare the spatial precision of both correction methods under varying terrain conditions. The results show a difference in mapping accuracy between RTK Radio and RTK NTRIP aerial photographs, with RTK Radio achieving 0.683 accuracy and 0.450 RMSE, while RTK NTRIP reached 0.563 accuracy and 0.371 RMSE. RTK Radio is more suitable for areas lacking CORS access but still requires GCP verification. RTK NTRIP performs better in urban areas with strong CORS networks. Combining both methods with adequate GCPs provides an effective solution for mapping in varied or densely vegetated terrains.